(untitled) (Research, Society and Development, 2024)
Gunshot wounds may cause extensive damage to the facial skeleton, generating complex fractures. Cases of great bone comminution and poor stability can be a challenge with rigid internal fixation. Thus, the use of an external fixator is indicated. The aim of this study is to report a case of a wrist external fixator for initial treatment of a gunshut injury. A 58-year-old male patient was found on the street with extensive comminution and significant mobility of the mandibular bone, tooth loss, crown-root fractures, multiple metal fragments and a firearm projectile lodged in his face. The treatment implemented was surgical debridement with removal of foreign particles, unviable fragments and submental projectile. Next, wrist external fixator was installed bilaterally in the mandible. Good stability of the bone segments was achieved, in addition to preventing bone displacement into the airways. The use of an external fixator is a viable alternative for Traumatology services and can be useful in urgent cases like this one, allowing subsequent refined reconstructions.